Tidying up the mess: lectotype selections, synonyms, a new status and a new species in Syngonanthus sect. Carphocephalus (Eriocaulaceae) - Watanabe, Mauricio Takashi Coutinho; Hensold, Nancy; Sano, Paulo Takeo (Phytotaxa, 2015)
Novelties and nomenclatural issues in Syngonanthus sect. Carphocephalus (Eriocaulaceae) are presented here. This study is based on analyses of herbarium materials and field observations. Syngonanthus sect. Carphocephalus contains 13 species, all restricted to the Americas. Some species are widely distributed, such as S. caulescens, but most are rare or only known from the holotype. This taxonomic treatment presents new synonyms (S. inundatus and S. yacuambensis), lectotype selections for six names (Syngonanthus sect. Carphocephalus, S. appressus, S. hygrotrichus, S. inundatus, S. peruvianus, and S. rhizonema), nomenclatural changes (S. caulescens var. discretifolius) and a new species (S. mollis), from S. sect. Carphocephalus.